IINCIDENCE OF POST-OPERATIVE NAUSEA AND VOMITING IN LAPAROSCOPIC CHOLECYSTECTOMY WITH A SINGLE DOSE OF PREOPERATIVE DEXAMETHASONE - NAEEMI, MF (Biological and Clinical Sciences Research Journal, 2023)
and vomiting (PONV). Dexamethasone, a synthetic glucocorticoid with potent anti-inflammatory, immune-modulating, analgesic, and anti-emetic effects, effectively reduces the incidence of PONV after laparoscopic cholecystectomy. In this double-blind, placebo-controlled study, we aimed to investigate the efficacy of a single 8 mg dose of dexamethasone in preventing PONV in patients undergoing laparoscopic cholecystectomy. Sixty patients were randomized into two groups: group A, who received an 8 mg dexamethasone injection in a 2-ml preparation, and group B, who received normal saline during induction. Both groups received standardized anesthesia. Post-operatively, the incidence of nausea and vomiting was observed in both groups. Our study's findings indicate that no substantial variances were observed between the two cohorts in terms of medical or demographic factors. However, a lower proportion of patients in group A exhibited post-operative nausea and vomiting (PONV), while group B had a higher demand for anti-emetic medications to alleviate PONV symptoms. Thus, we can infer that administering a solitary dose of dexamethasone before laparoscopic cholecystectomy can reduce the risk of post-operative complications in patients.